2005
DOI: 10.1177/0310057x0503300413
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns in the Acute Pain Service: Epidural versus Patient-controlled Analgesia

Abstract: This study involved an audit and a survey of the Acute Pain Service at Princess Alexandra Hospital. It was found in the audit that the relative choice of epidural analgesia had declined by 50% over the five-year time period of 1998-2003. The survey of consultants showed that 82% of them had changed their practice and that they were performing fewer epidural anaesthetics. Two of the most common reasons given for this change in practice related to fear of litigation (34%) and lack of evidence (21%). These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…We found that for specific surgical indications, epidural analgesia remains frequently used, although 55% of respondents reported a decreasing trend in overall use of perioperative epidural analgesia. This finding is in accordance with previous studies that reported decreasing trends in perioperative epidural use . In contrast, epidural procedures for labour analgesia are gaining in popularity in the Netherlands.…”
Section: Discussionsupporting
confidence: 92%
“…We found that for specific surgical indications, epidural analgesia remains frequently used, although 55% of respondents reported a decreasing trend in overall use of perioperative epidural analgesia. This finding is in accordance with previous studies that reported decreasing trends in perioperative epidural use . In contrast, epidural procedures for labour analgesia are gaining in popularity in the Netherlands.…”
Section: Discussionsupporting
confidence: 92%
“…Other reasons cited for change reflect the issues raised in the editorial, such as difficulty with fluid management and maintenance of vasopressor regimens on standard wards. Our findings concur with data from Queensland, Australia where a survey showed 82% of specialists were using more patient‐controlled analgesia techniques over epidural analgesia [4].…”
supporting
confidence: 90%
“…In conclusion, this audit has shown a significant drop in epidural rates that occurred around the time of the MASTER trial's publication. In combination with similar work performed in Australia 11 , the results strongly suggest that selective interpretation of the available evidence-base for epidural anaesthesia and analgesia has resulted in a marked change in local practice in this field. However, given the changing role of epidural anaesthesia and analgesia, the focus on patient-centred outcomes and increasing fiscal pressures, it will be interesting to see if the rate of epidural anaesthesia and analgesia increases again.…”
Section: Discussionsupporting
confidence: 55%
“…The findings of this trial have been well publicised. Work done in Queensland found that 88% of specialists had read the paper 11 .…”
mentioning
confidence: 99%